Negative electrode active material for secondary battery and secondary battery
The employment of silicate composite particles with an amorphous lithium silicate phase and dispersed silicon oxide and silicon particles addresses the inefficiencies and stress issues in existing silicon-based negative electrode active materials, resulting in enhanced cycle characteristics and capacity retention.
Patent Information
- Application Number
- JP2021566843
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-10-15
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2040-10-15
AI Technical Summary
Existing negative electrode active materials for secondary batteries, particularly those containing silicon, suffer from low initial charge and discharge efficiency due to large irreversible capacity and stress-induced cracking, which deteriorates charge/discharge cycle characteristics.
The use of silicate composite particles as negative electrode active material, comprising crystalline silicon particles, an amorphous phase containing Li, O, and Si elements, and a silicon oxide phase, where the silicon oxide phase and silicon particles are dispersed within the amorphous phase, alleviates stress and suppresses cracking.
This configuration enhances the charge/discharge cycle characteristics and reduces irreversible capacity, leading to improved battery performance with higher capacity retention over multiple cycles.
Smart Images

Figure 0007660301000002 
Figure 0007660301000003 
Figure 0007660301000004
Abstract
Description
[Technical field]
[0001] The present disclosure primarily relates to improvements in negative electrode active materials for secondary batteries. [Background technology]
[0002] In recent years, secondary batteries such as non-aqueous electrolyte secondary batteries have been expected to be used for small consumer applications, power storage devices, and power sources for electric vehicles because of their high voltage and high energy density. As there is a demand for higher energy density batteries, there are expectations for the use of materials containing silicon, which alloys with lithium, as negative electrode active materials with high theoretical capacity density.
[0003] However, silicon-containing materials have a problem in that their initial charge-discharge efficiency (particularly the ratio of the initial discharge capacity to the initial charge capacity) is low due to their large irreversible capacity. Therefore, various techniques have been proposed for introducing lithium equivalent to the irreversible capacity into silicon-containing materials in advance. Specifically, it has been proposed to use composite particles containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase (Patent Document 1). The silicon particles contribute to the charge-discharge reaction (reversible absorption and release of lithium).
[0004] The composite particles are produced, for example, by sintering a mixture of glassy lithium silicate powder and silicon particles in a high-temperature, high-pressure atmosphere. In this case, the lithium silicate phase has crystallinity, and a clear peak derived from lithium silicate appears in the X-ray diffraction pattern. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2015-153520 A Summary of the Invention
[0006] It is known that the silicon particles of the above composite particles expand and contract to a large extent due to the absorption and release of lithium during charging and discharging. Therefore, the expansion and contraction of the silicon particles causes a large stress in the lithium silicate phase surrounding the silicon particles, which causes cracks and fractures in the composite particles. As a result, the binding force between the composite particles and the surrounding binder is weakened, and in particular, the fractured composite particles lose the conductive path with the surrounding particles and become isolated. In addition, side reactions between the electrolyte and the silicon particles are promoted. As a result, this causes a deterioration in the charge and discharge cycle characteristics.
[0007] One aspect of the present disclosure relates to a negative electrode active material for a secondary battery, comprising silicate composite particles including crystalline silicon particles, an amorphous phase including Li, O, and Si elements, and a silicon oxide phase, wherein the silicon oxide phase and the silicon particles are dispersed within the amorphous phase.
[0008] Another aspect of the present disclosure relates to a secondary battery including a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, the negative electrode including a current collector and a negative electrode active material layer, and the negative electrode active material layer including the above-described negative electrode active material for secondary batteries.
[0009] By using the negative electrode active material of the present disclosure, a secondary battery having excellent charge / discharge cycle characteristics can be obtained. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a negative electrode active material (LSX particles) according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic perspective view of a secondary battery according to an embodiment of the present disclosure with a portion cut away. [Diagram 3] FIG. 3 is a diagram showing an example of a diffraction pattern of an LSX particle by XRD. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The negative electrode active material for secondary batteries according to the embodiment of the present disclosure includes crystalline silicon particles, an amorphous phase containing Li, O, and Si elements (hereinafter also referred to as "amorphous lithium silicate phase" or simply "lithium silicate phase"), and silicate composite particles (hereinafter also referred to as LSX particles) containing a silicon oxide phase. By using such a negative electrode active material, the stress caused by the expansion and contraction of the silicon particles is alleviated by the amorphous lithium silicate phase, and cracks and breaks in the composite particles can be suppressed. Thus, the deterioration of the charge-discharge cycle characteristics is suppressed.
[0012] In the LSX particle, a plurality of primary particles including a lithium silicate phase and silicon particles are bonded to form a secondary particle. Looking at the secondary particle as a whole, the LSX particle has a sea-island structure in which silicon particles, which are islands, are dispersed in the lithium silicate phase, which is the sea. It is possible to increase the capacity by controlling the amount of silicon particles dispersed in the lithium silicate phase, and since the silicon particles are dispersed in the lithium silicate phase, it is easy to suppress the expansion and contraction of the LSX particles during charging and discharging. Furthermore, since the lithium silicate phase is amorphous, the expansion and contraction of the LSX particles is significantly suppressed. Therefore, it is easy to achieve both high capacity and improved cycle characteristics of the battery.
[0013] Conventionally, composite particles can be produced by mixing lithium silicate powder and silicon particles, pulverizing the mixture with a ball mill or the like to form a composite, and sintering the pulverized mixture in a high-temperature and high-pressure atmosphere. The lithium silicate powder may be amorphous or crystalline. However, even when crystalline lithium silicate powder is used, the crystalline lithium silicate may be changed to amorphous by the application of shear force caused by stirring the mixture. The crystallinity of the lithium silicate is restored by sintering at high temperature, and composite particles in which silicon particles are dispersed in the crystalline lithium silicate phase are obtained.
[0014] In contrast, in this embodiment, composite particles are formed without sintering at high temperatures. If necessary, heat treatment and / or pressure treatment may be performed at a relatively low temperature (for example, 450° C. or less) at which lithium silicate does not crystallize. This suppresses the crystal growth of lithium silicate, and LSX particles in which silicon particles are dispersed in an amorphous lithium silicate phase are obtained. Since the lithium silicate phase of these LSX particles is amorphous, the charge capacity in the initial charge / discharge tends to increase. Furthermore, since there is a large amount of amorphous material that is more flexible than crystals, the lithium silicate phase can follow the expansion and contraction of silicon, and the frequency of silicon particles becoming isolated and unable to charge and discharge is reduced. As a result, the capacity decrease in the charge / discharge cycles after the first one is significantly suppressed. Therefore, when considering a large number of charge / discharge cycles, the LSX particles of this embodiment are advantageous.
[0015] The particle size distribution of the lithium silicate powder is expanded by the composite formed by pulverization. As a result, the mixture after pulverization contains a large amount of fine lithium silicate powder with a small particle size. In the conventional method, such fine powder is integrated with the lithium silicate phase of the composite particles by sintering at high temperature and high pressure. In contrast, in the method of the present embodiment, which does not involve sintering at high temperature and high pressure, the surface area of the LSX particles produced is large, which may lead to increased side reactions. For this reason, it is preferable to classify the mixture after stirring and remove the lithium silicate particles with a small particle size.
[0016] LSX particles are manufactured by crushing and compounding silicon and lithium silicate. When lithium silicate has less lithium and more silicon oxide, silicon oxide is generated during the lithium silicate manufacturing process, and although much of the silicon oxide becomes amorphous during the crushing process, fine crystalline silicon oxide precipitates during the subsequent heating process. Crystalline silicon oxide is stable and does not react with lithium ions during charging, so it does not become the key to irreversible reactions, and because it is fine, it does not interfere with the expansion and contraction of silicon particles.
[0017] On the other hand, if the LSX particles contain a large amount of lithium silicate crystals such as Li2Si2O5, the expansion and contraction of the particles can easily cause cracking. In addition, the lithium silicate phase is more flexible when it is amorphous than when it is crystalline, so it is more likely to follow the expansion and contraction of the silicon particles. Therefore, the presence of two phases, a crystalline silicon oxide phase and an amorphous lithium silicate phase, can further reduce the stress caused by the expansion and contraction of the silicon particles. This makes it possible to realize a negative electrode active material with good cycle characteristics and small irreversible capacity.
[0018] The silicon oxide phase may be present dispersedly within the amorphous lithium silicate phase within the LSX particles, i.e., the silicon oxide phase and silicon particles may each be present dispersedly within the amorphous lithium silicate phase.
[0019] In the diffraction pattern of the LSX particles of this embodiment by X-ray diffraction (XRD), peaks derived from silicon particles and silicon oxide phase may appear. On the other hand, peaks derived from lithium silicate do not appear substantially. Specifically, a peak derived from the Si(111) plane of the silicon particles may appear around 2θ=28°. In addition, a peak derived from the SiO2(011) plane of the silicon oxide phase may appear around 2θ=26°. The half-width W1 of the peak derived from the Si(111) plane of the silicon particles may be, for example, 0.3 or more and 1.5 or less. The half-width W2 of the peak derived from the SiO2(011) plane of the silicon oxide phase may be, for example, 0.2 or more and 0.6 or less. Note that Cu Kα rays are used as the X-rays used in the XRD method. The half-widths W1 and W2 refer to full widths at half maximum that indicate a range in which the value is half or more of the maximum value of the peak.
[0020] Figure 3 shows examples of XRD diffraction patterns of the LSX particles of this embodiment and conventional LSX particles. In Figure 3, the diffraction pattern of LSX particle X3 shown by the solid line relates to the LSX particles of this embodiment, and the diffraction pattern of LSX particle Y3 shown by the dashed line relates to the conventional LSX particles. Note that LSX particle X3 corresponds to Example 3 (battery A3) in the examples described later, and LSX particle Y3 corresponds to Comparative Example 3 (battery B3).
[0021] In both LSX particles X3 and Y3, peaks derived from the Si(111) plane of silicon particles are observed near 2θ = 28°. Also, peaks derived from the SiO2(011) plane of the silicon oxide phase are observed near 2θ = 26°. Furthermore, in LSX particle Y3, a peak derived from lithium silicate Li2Si2O5 is observed near 2θ = 24°. On the other hand, in LSX particle X3, there is no peak near 2θ = 24°. Although not observed in LSX particles X3 and Y3, a peak derived from lithium silicate Li2SiO3 may appear near 2θ = 19°. The peak near 2θ = 20° is a peak derived from SiO2.
[0022] In the XRD pattern, the peak derived from the Si(111) plane of silicon particles is separated, and the integrated intensity obtained by integrating the separated peak in the range of 2θ = 23° to 30° is defined as I1. Similarly, the peak derived from the SiO2(011) plane of the silicon oxide phase is separated, and the integrated intensity obtained by integrating the separated peak in the range of 2θ = 23° to 30° is defined as I2. The sum of I1 and I2 is defined as A. Furthermore, from the total integrated intensity I total in the range of 2θ = 23° to 30°, the integrated intensity excluding the peaks derived from silicon particles and the silicon oxide phase is defined as B. The integrated intensity B may include the contribution from crystalline lithium silicate. At this time, the ratio B / A of the integrated intensity B to the integrated intensity A may be 0.03 or less. In this case, the suppressing effect on the degradation of charge-discharge cycle characteristics is remarkable. The ratio B / A may be 0.02 or less, or 0.01 or less.
[0023] In LSX particles, the amorphous lithium silicate phase includes, for example, an oxide phase represented by the formula: Li 2z SiO 2+z (0 < z < 1). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z = 1 / 2 is preferable.
[0024] The lithium silicate phase may contain elements other than Li, Si, and O (oxygen). The lithium silicate phase may contain, for example, at least one element selected from the group consisting of alkali metal elements (excluding Li) and Group II elements.
[0025] By including an alkali metal element other than Li in the lithium silicate phase, crystallization becomes difficult, the viscosity in the molten state is low, and the fluidity is high. Therefore, even in a heat treatment at a low temperature, the gaps between silicon particles are easily filled, and dense composite particles are easily produced. The alkali metal element may be Na and / or K, which are inexpensive. The atomic ratio of the alkali element X (e.g., K) other than Li contained in the lithium silicate phase to Li: X / Li may be, for example, 0.1 to 7.1, and may be 0.4 to 5, or 0.7 to 2.
[0026] The lithium silicate phase may contain a Group II element. In general, the silicate phase exhibits alkalinity, but the Group II element has the effect of suppressing the elution of alkali metals from the silicate phase. Therefore, the slurry viscosity is easily stabilized when preparing a slurry containing a negative electrode active material. Therefore, the need for a treatment (e.g., an acid treatment) for neutralizing the alkaline components of the LSX particles is also reduced.
[0027] As the Group II element, at least one selected from the group consisting of Be, Mg, Ca, Sr, Ba and Ra can be used. Among them, Ca is preferable because it can improve the Vickers hardness of the lithium silicate phase and further improve the cycle characteristics. The content of the Group II element is, for example, 20 mol % or less, or may be 15 mol % or less, or may be 10 mol % or less, based on the total amount of elements other than O contained in the lithium silicate phase.
[0028] The lithium silicate phase may contain an element M other than the alkali metal elements and the group II elements. The element M may be at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W. Specifically, for example, B has a low melting point and is advantageous for improving the fluidity during sintering. Ca has the effect of increasing the hardness of the lithium silicate phase, although it reduces the ion conductivity. Al, Zr, Nb, Ta and La can improve the hardness while maintaining the ion conductivity. The content of the element M may be, for example, 10 mol% or less, or 5 mol% or less, based on the total amount of elements other than O contained in the lithium silicate phase.
[0029] The contents of B, Na, K and Al contained in the lithium silicate phase are determined by quantitative analysis in accordance with JIS R3105 (1995) (analysis method for borosilicate glass), and the Ca content is determined by quantitative analysis in accordance with JIS R3101 (1995) (analysis method for soda-lime glass).
[0030] The other elements contained are determined by the following method. First, a sample of the lithium silicate phase or LSX particles containing it is completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid, and sulfuric acid), and the carbon remaining in the solution is filtered off. The filtrate is then analyzed by inductively coupled plasma atomic emission spectrometry (ICP-AES) to measure the spectral intensity of each element. Next, a calibration curve is created using commercially available standard solutions of the elements, and the content of each element contained in the lithium silicate phase is calculated.
[0031] In the silicate composite particles, there exist a lithium silicate phase, a silicon oxide phase, and silicon particles, and these can be distinguished and quantified by using Si-NMR. The Si content obtained by ICP-AES as described above is the sum of the Si amount constituting the silicon particles, the Si amount in the lithium silicate phase, and the Si amount in the silicon oxide phase. On the other hand, the Si amount constituting the silicon particles can be quantified separately by using Si-NMR. Therefore, the Si amount in the lithium silicate phase can be quantified by subtracting the Si amount constituting the silicon particles and the Si amount in the silicon oxide phase from the Si content obtained by ICP-AES. For the standard substance required for quantification, a mixture containing a silicate phase and silicon particles with a known Si content in a predetermined ratio may be used.
[0032] The following shows the desirable measurement conditions for Si-NMR.
[0033] <Si-NMR Measurement Conditions> Measuring device: Solid nuclear magnetic resonance spectrometer (INOVA-400) manufactured by Varian Probe: Varian 7mm CPMAS-2 MAS: 4.2 kHz MAS speed: 4 kHz Pulse: DD (45° pulse + signal acquisition time 1H decoupling) Repetition time: 1200 sec to 3000 sec Observation width: 100 kHz Observation center: Around -100 ppm Signal acquisition time: 0.05 sec Number of integrations: 560 Sample amount: 207.6 mg For increasing the capacity and improving the cycle characteristics, the content of silicon particles in the LSX particles may be, for example, 30 mass% or more and 80 mass% or less. By setting the content of silicon particles to 30 mass% or more, the proportion occupied by the lithium silicate phase becomes smaller, and the initial charge-discharge efficiency is likely to be improved. By setting the content of silicon particles to 80 mass% or less, it becomes easier to reduce the degree of expansion and contraction of the LSX particles during charge and discharge.
[0034] The silicon particles dispersed in the lithium silicate phase have a particulate phase of simple silicon (Si) and are composed of single or multiple crystallites. The crystallite size of the silicon particles is preferably 30 nm or less. When the crystallite size of the silicon particles is 30 nm or less, the volume change due to the expansion and contraction of the silicon particles accompanying charging and discharging can be reduced, and the cycle characteristics can be further improved. For example, when the silicon particles contract, voids are formed around the silicon particles, reducing the contact points with the surroundings of the particles, suppressing the isolation of the particles, and suppressing the decrease in charge and discharge efficiency due to the isolation of the particles. The lower limit of the crystallite size of the silicon particles is not particularly limited, but is, for example, 5 nm.
[0035] The crystallite size of the silicon particles is more preferably 2 nm or more and 30 nm or less, and even more preferably 2 nm or more and 20 nm or less. When the crystallite size of the silicon particles is 20 nm or less, the expansion and contraction of the silicon particles can be made uniform, and the cycle characteristics can be improved by reducing fine cracks in the particles due to the expansion and contraction of the silicon particles during charging and discharging. The crystallite size of the silicon particles is calculated by the Scherrer formula from the half-width of the diffraction peak assigned to the Si(111) plane in the X-ray diffraction (XRD) pattern of the silicon particles.
[0036] At least a part of the surface of the LSX particles may be coated with a conductive material. The lithium silicate phase has poor electronic conductivity, so the conductivity of the LSX particles tends to be low. However, by coating the surface of the secondary particles of the lithium silicate phase with a conductive material to form a conductive layer, the conductivity of the LSX particles can be dramatically increased. The conductive material is preferably a carbon material. The carbon material preferably contains at least one selected from the group consisting of carbon compounds and carbonaceous materials.
[0037] The thickness of the conductive layer is preferably thin enough not to substantially affect the average particle size of the LSX particles. In consideration of ensuring electrical conductivity and diffusibility of lithium ions, the thickness of the conductive layer is preferably 1 to 200 nm, more preferably 5 to 100 nm. The thickness of the conductive layer can be measured by observing the cross section of the LSX particles using a SEM or a TEM (transmission electron microscope).
[0038] Examples of carbon compounds include compounds containing carbon and hydrogen, and compounds containing carbon, hydrogen, and oxygen. Examples of carbonaceous materials include amorphous carbon with low crystallinity and graphite with high crystallinity. Examples of amorphous carbon include carbon black, coal, coke, charcoal, and activated carbon. Examples of graphite include natural graphite, artificial graphite, and graphitized mesophase carbon particles. Among these, amorphous carbon is preferred because it has low hardness and a large buffering effect against silicon particles that change in volume during charging and discharging. The amorphous carbon may be either easily graphitized carbon (soft carbon) or difficult to graphitize carbon (hard carbon). Examples of carbon black include acetylene black and ketjen black.
[0039] LSX particles can be extracted from a battery by the following method. First, the battery is disassembled to remove the negative electrode, which is washed with anhydrous ethyl methyl carbonate or dimethyl carbonate to remove the electrolyte. Next, the negative electrode mixture is peeled off from the copper foil and crushed in a mortar to obtain a sample powder. Next, the sample powder is dried in a dry atmosphere for 1 hour and immersed in weakly boiled 6M hydrochloric acid for 10 minutes to remove alkali metals such as Na and Li that may be contained in the binder, etc. Next, the sample powder is washed with ion-exchanged water, filtered, and dried at 200 °C for 1 hour. After that, it is heated to 900 °C in an oxygen atmosphere to remove the carbon components, and only the LSX particles can be isolated.
[0040] The cross-sectional observation of LSX particles can be carried out, for example, by the following method. First, disassemble the battery, take out the negative electrode, and obtain the cross-section of the negative electrode mixture layer using a cross-section polisher (CP). Observe the cross-section of the negative electrode mixture layer using a scanning electron microscope (SEM). Randomly select 10 LSX particles with a maximum particle diameter of 5 μm or more from the cross-sectional image of the backscattered electron image of the negative electrode mixture layer, and perform elemental (e.g., carbon) mapping analysis on each of them using energy-dispersive X-ray (EDX). Calculate the contained area of the target element using image analysis software. The observation magnification is preferably 2000 to 20000 times. Obtain the average of the measured values of the contained areas of a predetermined element for the 10 obtained particles.
[0041] Note that during the charge-discharge process, a film is formed on the surface of LSX particles due to the decomposition of the electrolyte or the like. In addition, as will be described later, LSX particles may further include a conductive layer that covers the surface of the composite particles. Therefore, the mapping analysis by EDX is performed on the range within 1 μm from the peripheral edge of the cross-section of LSX particles so that a thin film or a conductive layer is not included in the measurement range. The distribution state of the carbon material inside the LSX particles can also be confirmed by the mapping analysis by EDX. Since it is difficult to distinguish from the decomposition products of the electrolyte at the end of the cycle, it is preferable to measure samples before or at the beginning of the cycle.
[0042] The measurement conditions for the desirable cross-sectional SEM-EDX analysis are shown below.
[0043] <SEM-EDX Measurement Conditions> Processing device: JEOL, SM-09010 (Cross Section Polisher) Processing conditions: acceleration voltage 6 kV Current value: 140 μA Vacuum degree: 1×10 -3 ~2×10 -3 Pa Measurement device: Electron microscope HITACHI SU-70 Acceleration voltage during analysis: 10 kV Field: Free mode Probe current mode: Medium Probe Current Range: High Anode Ap.:3 OBJ Ap.:2 Analysis area: 1 μm square Analysis software: EDAX Genesis CPS: 20500 Lsec:50 Time constant: 3.2 In addition, the quantitative determination of each element in the silicate composite particles contained in the negative electrode active material layer in a discharged state can be performed not only by SEM-EDX analysis, but also by Auger electron spectroscopy (AES), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy (XPS), etc.
[0044] Next, the method for producing the LSX particles will be described in detail.
[0045] Process (i) The raw material for lithium silicate is a raw material mixture containing a Si-containing raw material and a Li raw material in a predetermined ratio. The raw material mixture may contain the above-mentioned alkali metal element, group II element, and / or element M. A mixture of the above raw materials in a predetermined amount is melted, and the melt is passed through a metal roll to form flakes to produce lithium silicate. The flaked silicate is then crystallized by heat treatment in an air atmosphere at a temperature above the glass transition point and below the melting point. The flaked silicate can also be used without being crystallized. It is also possible to produce silicate by a solid-phase reaction by firing a mixture of the above-mentioned raw materials in a predetermined amount at a temperature below the melting point without melting it.
[0046] Silicon oxide can be used as the Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as the Li raw material. These may be used alone or in combination of two or more. Raw materials for alkali metal elements, Group II elements, and element M include oxides, hydroxides, carbonates, hydrides, nitrates, sulfates, etc. of each element.
[0047] The Si raw material that has not reacted with the Li raw material may remain in the lithium silicate. The remaining Si raw material is dispersed in the lithium silicate as a silicon oxide phase.
[0048] Process (ii) Next, the lithium silicate is mixed with raw silicon to form a composite. For example, the composite particles are produced through the following steps (a) to (c).
[0049] Process (a) First, raw silicon powder and lithium silicate powder are mixed in a mass ratio of, for example, 20:80 to 95:5. The raw silicon may be coarse silicon particles having an average particle size of several μm to several tens of μm.
[0050] Process (b) Next, the mixture of raw silicon and lithium silicate is pulverized and compounded while being finely divided using a pulverizing device such as a ball mill. At this time, an organic solvent may be added to the mixture and wet-pulverized. A predetermined amount of the organic solvent may be charged into the pulverizing vessel at once at the beginning of the pulverization, or a predetermined amount of the organic solvent may be charged into the pulverizing vessel intermittently in multiple batches during the pulverization process. The organic solvent serves to prevent the material to be pulverized from adhering to the inner wall of the pulverizing vessel.
[0051] As the organic solvent, alcohols, ethers, fatty acids, alkanes, cycloalkanes, silicate esters, metal alkoxides, and the like can be used.
[0052] The raw silicon and lithium silicate may be separately pulverized and then mixed. Alternatively, silicon nanoparticles and amorphous lithium silicate nanoparticles may be produced and mixed without using a pulverizer. The nanoparticles may be produced by a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).
[0053] Process (c) Next, the finely divided mixture is classified to remove components with small particle diameters. For example, fine particles of lithium silicate with a particle diameter of 0.5 μm or less can be removed by classification. The classifier used for classification is not particularly limited as long as it can classify fine particles with a particle diameter of 0.5 μm or less. However, classification is generally performed by placing the fine particles in a fluid flow, applying a force (for example, inertial force or centrifugal force) to the fine particles through the fluid, and utilizing the difference in the force acting on the fine particles for each particle diameter. Therefore, the fluid (gas or liquid) used for classification must have low reactivity with lithium silicate. In this respect, a dry classifier using a gas as the fluid is preferably used as the classifier. However, if a liquid with low reactivity with lithium silicate is used as the fluid, a wet classifier may be used. The principle of classification of the classifier is also not particularly limited, and may be, for example, one that utilizes inertial force or one that utilizes centrifugal force. An elbow jet type classifier that utilizes the Coanda effect may be used.
[0054] Process (iii) Next, at least a part of the surface of the composite particles (secondary particles) may be coated with a conductive material to form a conductive layer. The conductive material is preferably electrochemically stable, and is preferably a conductive carbon material. Examples of a method for coating the surface of the composite particles with a conductive carbon material include a CVD method using a hydrocarbon gas such as acetylene or methane as a raw material, and a method of mixing coal pitch, petroleum pitch, phenol resin, etc. with the composite particles and heating to carbonize them. Carbon black may also be attached to the surface of the composite particles. The coating with the conductive carbon material can be performed, for example, by heating a mixture of the particles from which the fine particles have been removed and the conductive carbon material in an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.) at 700°C to 950°C.
[0055] Process (iv) A step of washing the composite particles (including those having a conductive layer on the surface) with an acid may be carried out. For example, by washing the composite particles with an acidic aqueous solution, it is possible to dissolve and remove trace amounts of alkaline components present on the surface of the composite particles that may be generated when the raw silicon and lithium silicate are combined. As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, or carbonic acid, or an aqueous solution of an organic acid such as citric acid or acetic acid can be used.
[0056] FIG. 1 shows a schematic cross section of an LSX particle 20 as an example of a negative electrode material.
[0057] The LSX particle 20 includes a base particle 23 composed of secondary particles formed by agglomeration of a plurality of primary particles 24. The base particle 23 (primary particle 24) includes an amorphous lithium silicate phase 21, silicon particles 22 dispersed within the lithium silicate phase 21, and a silicon oxide phase 28. The base particle 23 has a sea-island structure in which fine silicon particles are dispersed in the matrix of the lithium silicate phase 21. The surface of the base particle 23 may be covered with a conductive layer 26.
[0058] Both the lithium silicate phase 21 and the silicon particles 22 are constituted by an aggregation of fine primary particles. A silicon oxide phase 28 may also be dispersed in the lithium silicate phase 21. The SiO2 content in the base particles 23 measured by Si-NMR is preferably, for example, 30 mass% or less, and more preferably less than 7 mass%.
[0059] The base particle 23 may contain other components in addition to the lithium silicate phase 21, the silicon particles 22, the silicon oxide phase 28, and the carbon material. For example, from the viewpoint of improving the strength of the base particle 23, the base particle 23 may contain a reinforcing material such as an oxide such as ZrO2 or a carbide up to 10% by weight of the base particle 23.
[0060] The average particle size of the primary particles 24 is preferably 0.2 to 10 μm, more preferably 2 to 8 μm. This makes it easier to further relax the stress caused by the volume change of the silicon particles accompanying charging and discharging, and makes it easier to obtain good cycle characteristics. In addition, since the surface area of the LSX particles becomes appropriate, the capacity decrease due to the side reaction with the electrolyte is also suppressed.
[0061] The average particle size of the primary particles 24 is measured by observing the cross section of the negative electrode material using a SEM. Specifically, it is found by averaging the diameters of circles equivalent to the cross-sectional areas of any 100 primary particles 24 (circles having the same area as the cross-sectional areas of the primary particles).
[0062] The average particle size of the silicon particles 22 is 500 nm or less, preferably 200 nm or less, and more preferably 50 nm or less, before the first charge. By appropriately miniaturizing the silicon particles 22 in this way, the volume change during charging and discharging is reduced, and structural stability is improved. In addition, the expansion and contraction of the silicon particles is made uniform, and particle cracking is suppressed, thereby improving cycle characteristics. The average particle size of the silicon particles 22 is measured by observing the cross section of the negative electrode material using a SEM or TEM. Specifically, it is obtained by averaging the maximum diameters of 100 arbitrary silicon particles 22.
[0063] The secondary battery according to the embodiment of the present disclosure includes a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode. The negative electrode includes a current collector and a negative electrode active material layer including the negative electrode active material for secondary batteries. The negative electrode, positive electrode, electrolyte, and separator included in the secondary battery according to the embodiment of the present disclosure will be described below.
[0064] [Negative electrode] The negative electrode comprises, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed by applying a negative electrode slurry in which the negative electrode mixture is dispersed in a dispersion medium to the surface of the negative electrode current collector and drying it. The coating film after drying may be rolled as necessary. The negative electrode mixture layer may be formed on one surface or both surfaces of the negative electrode current collector.
[0065] The negative electrode mixture contains the above-mentioned LSX particle-containing negative electrode active material for secondary batteries as an essential component as a negative electrode active material, and may contain optional components such as a binder, a conductive agent, a thickener, etc. The silicon particles in the LSX particles can absorb many lithium ions, thereby contributing to a high capacity negative electrode.
[0066] The negative electrode active material may further contain other active material materials that electrochemically absorb and release lithium ions. For example, carbon-based active materials are preferable as other active material materials. Since the LSX particles expand and contract in volume with charging and discharging, when the ratio of the LSX particles in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode current collector with charging and discharging is likely to occur. On the other hand, by using the LSX particles and the carbon-based active material in combination, it is possible to achieve excellent cycle characteristics while imparting the high capacity of the silicon particles to the negative electrode. The ratio of the LSX particles to the total of the LSX particles and the carbon-based active material is, for example, preferably 0.5 to 15 mass%, more preferably 1 to 5 mass%. This makes it easier to achieve both high capacity and improved cycle characteristics.
[0067] Examples of carbon-based active materials include graphite, graphitizable carbon (soft carbon), and non-graphitizable carbon (hard carbon). Among them, graphite is preferable because it has excellent charge / discharge stability and low irreversible capacity. Graphite means a material having a graphite-type crystal structure, and includes, for example, natural graphite, artificial graphite, and graphitized mesophase carbon particles. The carbon-based active materials may be used alone or in combination of two or more.
[0068] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but is preferably 1 to 50 μm, more preferably 5 to 20 μm, from the viewpoint of the balance between the strength and weight reduction of the negative electrode.
[0069] Examples of the binder include fluororesin, polyolefin resin, polyamide resin, polyimide resin, vinyl resin, styrene-butadiene copolymer rubber (SBR), polyacrylic acid and its derivatives. These may be used alone or in combination of two or more. Examples of the conductive agent include carbon black, conductive fiber, carbon fluoride, organic conductive material, etc. These may be used alone or in combination of two or more. Examples of the thickener include carboxymethyl cellulose (CMC), polyvinyl alcohol, etc. These may be used alone or in combination of two or more.
[0070] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and a mixture of these.
[0071] [Positive electrode] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which the positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying it. The coating film after drying may be rolled as necessary. The positive electrode mixture layer may be formed on one surface of the positive electrode current collector or on both surfaces.
[0072] The positive electrode mixture contains a positive electrode active material as an essential component, and may contain a binder, a conductive agent, and the like as optional components.
[0073] The positive electrode active material may be a lithium composite metal oxide. For example, Li a CoO2, Li a NiO2, Li a MnO2, Li a Co b Ni 1-b O2, Li a Co b M 1-b O c , Li a Ni 1-b M b Oc , Li a Mn2O4, Li a Mn 2-b M b O 4、 LiMePO 4、 Li2MePO4F is an example. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, and B. Me contains at least a transition element (for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni). Here, 0≦a≦1.2, 0≦b≦0.9, and 2.0≦c≦2.3. The value a, which indicates the molar ratio of lithium, is a value immediately after the active material is produced, and increases or decreases by charging and discharging.
[0074] The binder and conductive agent may be the same as those exemplified for the negative electrode. As the conductive agent, graphite such as natural graphite or artificial graphite may be used.
[0075] The shape and thickness of the positive electrode current collector can be selected from the shape and range corresponding to those of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, and titanium.
[0076] [Electrolyte] The electrolyte contains a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolyte is, for example, 0.5 to 2 mol / L. The electrolyte may contain known additives.
[0077] The solvent used may be an aqueous solvent or a non-aqueous solvent. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, and cyclic carboxylates. Examples of the cyclic carbonates include propylene carbonate (PC) and ethylene carbonate (EC). Examples of the chain carbonates include diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). Examples of the cyclic carboxylates include γ-butyrolactone (GBL) and γ-valerolactone (GVL). The non-aqueous solvents may be used alone or in combination of two or more.
[0078] Examples of lithium salts include lithium salts of chlorine-containing acids (LiClO4, LiAlCl4, LiB 10 Cl 10 etc.), lithium salts of fluorine-containing acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorine-containing acid imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc., can be used. One type of lithium salt may be used alone, or two or more types may be used in combination.
[0079] [Separator] Usually, it is desirable to interpose a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation properties. As the separator, a microporous thin film, a woven fabric, a nonwoven fabric, etc. can be used. As the material of the separator, for example, a polyolefin such as polypropylene or polyethylene can be used.
[0080] An example of the structure of the secondary battery is a structure in which an electrode group formed by winding a positive electrode and a negative electrode with a separator interposed therebetween and an electrolyte are housed in an exterior body. Alternatively, instead of a wound type electrode group, other types of electrode groups may be applied, such as a stacked type electrode group formed by stacking a positive electrode and a negative electrode with a separator interposed therebetween. The secondary battery may be in any form, such as a cylindrical type, a square type, a coin type, a button type, a laminate type, or the like.
[0081] FIG. 2 is a schematic perspective view, with a portion cut away, of a prismatic secondary battery according to an embodiment of the present disclosure.
[0082] The battery includes a bottomed rectangular battery case 4, an electrode group 1 and an electrolyte housed in the battery case 4, and a sealing plate 5 that seals the opening of the battery case 4. The electrode group 1 includes a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator interposed therebetween. The negative electrode, positive electrode, and separator are wound around a flat winding core, and the electrode group 1 is formed by removing the winding core. The sealing plate 5 includes a liquid injection port closed with a plug 8, and a negative electrode terminal 6 insulated from the sealing plate 5 by a gasket 7.
[0083] One end of a negative electrode lead 3 is attached to the negative electrode current collector of the negative electrode by welding or the like. One end of a positive electrode lead 2 is attached to the positive electrode current collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to a negative electrode terminal 6. The other end of the positive electrode lead 2 is electrically connected to a sealing plate 5. A resin frame is disposed on the upper part of the electrode group 1 to separate the electrode group 1 from the sealing plate 5 and to separate the negative electrode lead 3 from the battery case 4.
[0084] <Example> Hereinafter, the present disclosure will be specifically described based on examples and comparative examples, but the present disclosure is not limited to the following examples.
[0085] <Example 1> [Preparation of LSX particles] Process (i) Lithium carbonate and silicon dioxide were mixed to a molar ratio of Li2CO3:SiO2 = 34:66, the mixture was melted in an inert atmosphere at 1500°C for 5 hours, the molten liquid was passed through a metal roller to form flakes, and then heat-treated at 750°C for 5 hours to obtain a lithium silicate composite oxide that exists as a mixed phase of amorphous and crystalline phases. The obtained lithium silicate composite oxide was pulverized to an average particle size of 10 μm.
[0086] Process (ii) A lithium silicate composite oxide with an average particle size of 10 μm was mixed with raw material silicon (3N, average particle size of 10 μm) in a mass ratio of 70:30. The mixture was loaded into a pot (made of SUS, volume: 500 mL) of a planetary ball mill (manufactured by Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed in, the lid was closed, and the mixture was milled at 200 rpm for 25 hours in an inert atmosphere.
[0087] The mixture was then classified using an elbow jet classifier to remove fine particles with a particle size less than 0.5 μm.
[0088] The classified mixture was then mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation), and the mixture was fired at 800°C for 5 hours in an inert gas atmosphere to coat the surfaces of the LSX particles with conductive carbon to form a conductive layer. The amount of the conductive layer was 5 mass% based on the total mass of the LSX particles and the conductive layer. A sieve was then used to obtain LSX particles (secondary particles) with an average particle size of 5 μm and a conductive layer. XRD analysis was performed on the LSX particles to measure the presence or absence of peaks derived from Si, SiO2, Li2Si2O5, and Li2SiO3.
[0089] [Preparation of negative electrode] LSX particles and graphite were mixed in a mass ratio of 5:95 and used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), styrene-butadiene rubber (SBR), and lithium polyacrylate were mixed in a mass ratio of 96.5:1:1.5:1, water was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a negative electrode slurry. Next, 1 m of the mixture was applied to the surface of the copper foil. 2 The negative electrode slurry was applied so that the mass of the negative electrode mixture per sheet was 190 g, the coating was dried, and then rolled to form a copper foil with a density of 1.5 g / cm on both sides. 3 Thus, a negative electrode having a negative electrode mixture layer of the above formula was fabricated.
[0090] [Preparation of positive electrode] Lithium cobalt oxide, acetylene black, and polyvinylidene fluoride were mixed in a mass ratio of 95:2.5:2.5, N-methyl-2-pyrrolidone (NMP) was added, and the mixture was stirred using a mixer (TK Hivismix, manufactured by Primix Corporation) to prepare a positive electrode slurry. The positive electrode slurry was then applied to the surface of an aluminum foil, the coating was dried, and the mixture was rolled to form a positive electrode slurry having a density of 3.6 g / cm on both sides of the aluminum foil. 3 A positive electrode having a positive electrode mixture layer of the above formula was fabricated.
[0091] [Preparation of electrolyte] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.
[0092] [Preparation of secondary battery] A tab was attached to each electrode, and the positive and negative electrodes were spirally wound with a separator interposed therebetween so that the tabs were located at the outermost periphery to prepare an electrode group. The electrode group was inserted into an exterior body made of an aluminum laminate film and vacuum dried at 105°C for 2 hours. After that, a nonaqueous electrolyte was poured in and the opening of the exterior body was sealed to obtain a secondary battery A1.
[0093] <Example 2> In step (i), the mixing ratio of lithium carbonate and silicon dioxide was changed to a molar ratio of Li2CO3:SiO2=27:73.
[0094] Other than this, LSX particles were prepared in the same manner as in Example 1, a negative electrode including the LSX particles was fabricated, and a secondary battery A2 was obtained.
[0095] <Example 3> In step (i), lithium carbonate (Li2CO3), silicon dioxide (SiO2), a mixture of calcium carbonate (CaCO3) and magnesium carbonate (MgCO3), and a mixture of boric acid (H3BO3), aluminum hydroxide (Al2(OH)3) and lanthanum oxide (La2O3) were mixed in a molar ratio of 20:70:2:8, the mixture was melted at 1500°C for 5 hours in an inert atmosphere, the molten liquid was passed through a metal roller to form flakes, and a lithium silicate composite oxide existing as a mixed phase of amorphous and crystalline phases was obtained by heat treatment at 750°C for 5 hours.
[0096] Except for this, LSX particles were prepared in the same manner as in Example 1, a negative electrode including the LSX particles was fabricated, and a secondary battery A3 was obtained.
[0097] <Comparative Example 1> In Example 1, the mixing ratio of lithium carbonate and silicon dioxide in step (i) was changed to a molar ratio of Li2CO3:SiO2=50:50.
[0098] In addition, in step (ii), the crushed mixture was not classified, and the crushed mixture was sintered at 600°C for 4 hours in an inert atmosphere while applying pressure to the mixture using a hot press, thereby obtaining a sintered body of the mixture.
[0099] The sintered body was then crushed and passed through a 40 μm mesh, after which it was mixed with coal pitch (MCP250, manufactured by JFE Chemical Corporation), and the mixture was fired at 800°C for 5 hours in an inert atmosphere to coat the surfaces of the LSX particles with conductive carbon to form a conductive layer. The amount of the conductive layer was 5 mass% based on the total mass of the LSX particles and the conductive layer. Then, using a sieve, LSX particles (secondary particles) with an average particle size of 5 μm and provided with a conductive layer were obtained.
[0100] Using the above LSX particles, a negative electrode was produced in the same manner as in Example 1, to obtain a secondary battery B1.
[0101] <Comparative Example 2> In Comparative Example 1, the mixing ratio of lithium carbonate and silicon dioxide in step (i) was changed to a molar ratio of Li2CO3:SiO2=34:66.
[0102] Except for this, LSX particles were prepared in the same manner as in Comparative Example 1, a negative electrode including the LSX particles was fabricated, and a secondary battery B2 was obtained.
[0103] <Comparative Example 3> In step (i), lithium carbonate (Li2CO3), silicon dioxide (SiO2), a mixture of calcium carbonate (CaCO3) and magnesium carbonate (MgCO3), and a mixture of boric acid (H3BO3), aluminum hydroxide (Al2(OH)3) and lanthanum oxide (La2O3) were mixed in a molar ratio of 20:70:2:8, the mixture was melted at 1500°C for 5 hours in an inert atmosphere, the molten liquid was passed through a metal roller to form flakes, and a lithium silicate composite oxide existing as a mixed phase of amorphous and crystalline phases was obtained by heat treatment at 750°C for 5 hours.
[0104] Except for this, LSX particles were prepared in the same manner as in Comparative Example 1, a negative electrode including the LSX particles was fabricated, and a secondary battery B3 was obtained.
[0105] The following evaluations were carried out for each of the batteries of the Examples and Comparative Examples.
[0106] [Initial discharge capacity] Each battery was charged at a constant current of 1 It (800 mA) at 25° C. until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 It (40 mA). After a rest period of 10 minutes, constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V, and the discharge capacity was evaluated. The discharge capacity of Example 1 was set to 100, and the others were normalized.
[0107] [Charge / discharge cycle test] The battery was repeatedly charged and discharged under the following conditions.
[0108] <Charging> At 25° C., constant current charging was performed at a current of 1 It (800 mA) until the voltage reached 4.2 V, and then constant voltage charging was performed at a voltage of 4.2 V until the current reached 1 / 20 It (40 mA).
[0109] <Discharge> At 25° C., constant current discharge was performed at a current of 1 It (800 mA) until the voltage reached 2.75 V.
[0110] The rest period between charging and discharging was 10 minutes. The ratio of the discharge capacity at the 100th cycle to the discharge capacity at the 1st cycle was defined as the cycle retention rate, and the number of cycles in Example 1 was set to 100, and the others were normalized. If the cycle retention rate was 90 or more, the charge-discharge cycle characteristics were determined to be good.
[0111] The evaluation results for each of the batteries A1 to A3 and B1 to B3 are shown in Table 1. In addition, Table 1 also shows the presence or absence of a peak derived from the Si(111) plane, a peak derived from the SiO2 (011) plane, and a peak derived from lithium silicate (Li2Si2O5, Li2SiO3) by XRD analysis of the LSX particles used as the negative electrode active material of each battery, and the half-width (° / 2θ) of the peak if each peak is present. Table 1 also shows the ratio B / A of the above-mentioned integrated intensity for the LSX particles used as the negative electrode active material of each battery.
[0112] [Table 1]
[0113] As can be seen from Table 1, the batteries A1 to A3, which have an amorphous lithium silicate phase in the LSX particles and do not have peaks derived from Li2Si2O5 and Li2SiO3, exhibited higher initial discharge capacities and cycle retention rates than the batteries B1 to B3, which have a crystalline lithium silicate phase. [Industrial Applicability]
[0114] The present disclosure can provide a nonaqueous electrolyte secondary battery having high capacity and good charge / discharge cycle characteristics. The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like. [Explanation of symbols]
[0115] 1 electrode group 2 Positive Lead 3 Negative lead 4 Battery case 5 Sealing plate 6 Negative terminal 7 Gasket 8. Sealing 20 LSX particles 21 Lithium silicate phase 22 Silicon particles 23 Mother particle 24 Primary particles 26 Conductive Layer 28 Silicon oxide phase
Claims
1. The silicate composite particle includes a crystalline silicon particle, an amorphous phase including Li, O, and Si elements, and a silicon oxide phase; The silicon oxide phase and the silicon particles are dispersed within the amorphous phase, A negative electrode active material for a secondary battery, which has no peak derived from lithium silicate in a diffraction pattern obtained by X-ray diffraction (XRD).
2. In the diffraction pattern by X-ray diffraction (XRD), the integrated intensity I of the peak originating from the Si (111) plane of the silicon particle, which appears in the range of 2θ = 27 ° to 30 ° 1 and SiO of the silicon oxide phase appearing in the range of 2θ = 25° to 27°. 2 Integrated intensity I of the peak originating from the (011) plane 2 The peak derived from the Si(111) plane of the silicon particle and the SiO of the silicon oxide phase with respect to the total A 2 2. The negative electrode active material for secondary batteries according to claim 1, wherein a ratio B / A of an integrated intensity B excluding a peak derived from a (011) plane is 0.03 or less in an integral range of 23° to 30°.
3. A silicate composite particle including a crystalline silicon particle, an amorphous phase including Li, O, and Si elements, and a silicon oxide phase, The silicon oxide phase and the silicon particles are dispersed within the amorphous phase, a ratio B / A of an integrated intensity B excluding peaks originating from the Si(111) plane of the silicon particles and peaks originating from the SiO 2 (011) plane of the silicon oxide phase to a sum A of an integrated intensity I 1 of a peak originating from the Si(111) plane of the silicon particles appearing in the range of 2θ=27° to 30° and an integrated intensity I 2 of a peak originating from the SiO 2 (011) plane of the silicon oxide phase appearing in the range of 2θ=25° to 27° in a diffraction pattern obtained by X-ray diffraction (XRD), is 0.03 or less in the integral range of 23° to 30°.
4. In a diffraction pattern obtained by X-ray diffraction (XRD), the half-width W of a diffraction peak at about 2θ=28° originating from the Si(111) plane of the silicon particle 1 The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein is 0.3 or more and 1.5 or less.
5. In the diffraction pattern by X-ray diffraction (XRD), the silicon oxide phase SiO 2 The half-width W of the diffraction peak at around 2θ=26° originating from the (011) plane 2 The negative electrode active material for a secondary battery according to any one of claims 1 to 4, wherein is 0.2 or more and 0.6 or less.
6. The negative electrode active material for a secondary battery according to any one of claims 1 to 5, wherein the amorphous phase further contains at least one element selected from the group consisting of alkali metal elements other than Li and group II elements.
7. The amorphous phase further contains an element M, The element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W. The negative electrode active material for secondary batteries according to any one of claims 1 to 6.
8. A battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode; the negative electrode includes a current collector and a negative electrode active material layer, A secondary battery, wherein the negative electrode active material layer comprises the negative electrode active material for secondary batteries according to any one of claims 1 to 7.
Citation Information
Patent Citations
Powder for negative electrode of lithium ion secondary battery, and method of manufacturing the same
JP2015153520A
Negative electrode active material for nonaqueous electrolyte secondary battery
WO2019130787A1